Standardization and valorisation of digital educational materials - Divjak, Blaženka; Prišćan Sonja, Hoić-Božić, Nataša; Hudec, Goran Kukolja Taradi, Sunčana, Pervan, Petar; Špiranec, Sonja (2005)
According to results of the program “ Educational projects” , multidisciplinary team which led the program concluded that it is needed to take a lot of coordinated actions in order to encourage use of ICT in Croatian higher education system. The team recognized two main obstacles which can be cause for small number of university teachers who were using ICT in education process: lack of technical support for creation of educational materials and absence of procedure for valorisation of production of digital educational materials in the process of promotion of university teachers. In order to eliminate first obstacle CARNet established seven Referral centres for e-education which have been providing information and technical support for creation and application of digital materials in education process. After that, CARNet brought together another multidisciplinary team (mostly consisted of university teachers) with the goal to prepare a document which will (or could) be used by Croatian universities during categorisation, valorisation and evaluation of digital educational materials designed and prepared by their employees, university teachers. Beside, the document suggests how to describe, store, search and use digital educational materials with reference to creation of Croatian repository of digital educational materials. The paper will present the results of this project.
Projekt MZOS
ENG